2005
DOI: 10.1097/01.wnr.0000183899.85277.08
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanism of residual inhibition of tinnitus in cochlear implant users

Abstract: Residual inhibition is a transient suppression of tinnitus after auditory stimulation has stopped. We used positron emission tomography to study brain regions underlying residual inhibition in three tinnitus patients with cochlear implants and six normal hearing controls. Regional cerebral blood flow was measured and compared under two conditions: with tinnitus and during the residual inhibition of tinnitus. The right anterior middle and superior temporal gyri (Brodmann areas 21 and 38) were activated during r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 21 publications
2
38
1
Order By: Relevance
“…With respect to sample size, many neuroimaging studies draw conclusions about the underlying TI pathophysiology using group statistics with fewer than ten patients (e.g. Giraud et al, 1999;Kadner et al, 2002;Lockwood et al, 1998;Osaki et al, 2005). While such analyses might be adequate for characterising the common pathophysiology in that particular sample of patients, little can be inferred about the mechanisms underlying TI in the wider population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to sample size, many neuroimaging studies draw conclusions about the underlying TI pathophysiology using group statistics with fewer than ten patients (e.g. Giraud et al, 1999;Kadner et al, 2002;Lockwood et al, 1998;Osaki et al, 2005). While such analyses might be adequate for characterising the common pathophysiology in that particular sample of patients, little can be inferred about the mechanisms underlying TI in the wider population.…”
Section: Discussionmentioning
confidence: 99%
“…The neural effects of TI suppression achieved after residual inhibition has also been examined with PET (Osaki et al, 2005). Residual inhibition refers either to a partial or a complete temporary suppression of TI that lasts approximately 60 seconds after the cessation of a suprathreshold masking sound presented for a period of 30 to 60 seconds (Henry and Meikle, 2000).…”
Section: Human Neuroimaging Studiesmentioning
confidence: 99%
“…Positron emission tomography (PET) demonstrated that in patients with marked residual inhibitory effect of CI on tinnitus, the right anterior middle and superior temporal gyri were activated during residual inhibition after implant use, whereas the right cerebellum was activated during tinnitus perception [Osaki et al, 2005]. A further PET study revealed that the use of cochlear implants not only reduced the tinnitus-related activity in primary auditory and associate cortices but also in areas of the CNS associated with emotion (limbic system) and attention (dorsolateral prefrontal cortices) [Mirz et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Is this suppression due to the reversal of the assumed maladaptive plasticity or is it simply the shift in attention from the tinnitus to environmental sound and therefore less awareness that reduces tinnitus perception [Searchfield et al, 2012]? The former mechanism is supported by the presence of residual inhibition in many patients, a persistency in the tinnitus reduction after the stimulation is deactivated [Osaki et al, 2005;Arts et al, 2015]. Therefore, it should be possible to treat tinnitus by intracochlear electrical stimulation that does not directly encode acoustic sound.…”
Section: Introductionmentioning
confidence: 96%